Intestinal permeability and P‐glycoprotein‐mediated efflux transport of ticagrelor in Caco‐2 monolayer cells. (5th August 2016) - Marsousi, Niloufar; Doffey‐Lazeyras, Fabienne; Rudaz, Serge; Desmeules, Jules A.; Daali, Youssef
Abstract: Ticagrelor is the unique reversible oral antiplatelet drug commercialized today. During this study, the intestinal permeability of ticagrelor and its potential P‐glycoprotein (P‐gp)‐mediated active transport were assessed. To this end, bidirectional transport of ticagrelor was performed across Caco‐2 (human epithelial colorectal adenocarcinoma) monolayer model in the presence and absence of potent P‐gp inhibitor valspodar. Ticagrelor presented an apical–basolateral apparent permeability coefficient ( P app ) of 6.0 × 10 −6 cm/s. On the other hand, mean efflux ratio (ER) of 2.71 was observed for ticagrelor describing a higher efflux permeability compared to the influx component. Valspodar showed a significant inhibitory effect on the efflux of ticagrelor suggesting involvement of P‐gp in its oral disposition. Co‐incubation of the P‐gp inhibitor decreased the efflux P app of ticagrelor from 1.60 × 10 −5 to 1.13 × 10 −5 cm/s and decreased its ER by 70%. Results suggest a modest active transport of ticagrelor by P‐gp across the Caco‐2 cell monolayer. The co‐administration of ticagrelor with a P‐gp inhibitor seems altogether unlikely to have an extended impact on pharmacokinetics of ticagrelor and cause bleeding events in patients.